2021
DOI: 10.1099/jmm.0.001321
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dermatophytoses in Brazil: a systematic review

Abstract: Dermatophytosis is a common cutaneous mycosis worldwide whose prevalence in Brazil is still unknown. This systematic review has estimated the burden of dermatophytoses from updated literature data reported in the general Brazilian population. We used the following databases: Web of Science, Medline/PubMed, Embase, The Cochrane Library and Scopus for studies published between 2011 and 2020. Original articles with an emphasis on prevalence data for dermatophytosis in the Brazilian population, and diagnosed by cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
4
28
0
4
Order By: Relevance
“…An additional recent study showed that in diabetic patients in Kuwait, dermatophytes were the most common cause of onychomycosis [ 18 ]. In a systematic review of dermatophytes in Brazil, Trichophyton rubrum , T. interdigitale , and T. mentagrophytes were the most common species [ 19 ]. A study from Ethiopia showed that Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional recent study showed that in diabetic patients in Kuwait, dermatophytes were the most common cause of onychomycosis [ 18 ]. In a systematic review of dermatophytes in Brazil, Trichophyton rubrum , T. interdigitale , and T. mentagrophytes were the most common species [ 19 ]. A study from Ethiopia showed that Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%
“…The JHAH hospital in Dhahran is a 350-bed general hospital and provides medical care for about 160,000 individuals eligible for medical care. The study was approved by the Institutional Review Board (IRB) of Imam Abdulrahman Bin Faisal University (IRB-PGS-2018-03-175) and the IRB of JHAH (IRB # [18][19][20][21]. Fungal culture data from 2000 to 2019 period were obtained from the Laboratory Information System of the Mycology Laboratory at JHAH and from the electronic laboratory information system.…”
Section: Methodsmentioning
confidence: 99%
“…На это обратили внимание и авторы бразильского анализа многолетних исследований региональной заболеваемости дерматофитией -в среднем при обращаемости к дерматологу частота выявления микозов стоп и онихомикоза у них оказалась на уровне 25% -т.е. примерно столько же, сколько и в исследовании Achilles в 1997-1998 г. в среднем по Европе [10,11].…”
Section: глобальная и региональная эпидемиология дерматомикозовunclassified
“…Onychomycosis is a cutaneous fungal infection of the nail apparatus that is observed worldwide, the pooled prevalence of which can reach up to 25% as observed in Brazil [1]. Additionally it represents about 50% of all nail disorders [2].…”
Section: W Pracowni Mykologicznej Kliniki Dermatologii Wenerologii I Alergologii Gdańskiego Uniwersytetu Introductionmentioning
confidence: 99%
“…Dermatology Review/Przegląd Dermatologiczny 2021/4 WproWAdzenie Grzybica paznokci jest chorobą aparatu paznokciowego wywoływaną przez zakażenie grzybicze skóry. Występuje na całym świecie z częstością, która może sięgać 25%, jak zaobserwowano w Brazylii [1]. Grzybica paznokci stanowi około 50% wszystkich schorzeń aparatu paznokciowego [2].…”
unclassified